Deontic logic and legal systems - Navarro, Pablo E (Cambridge introductions to philosophy and law, 2014)
"Logic and law have a long history in common, but the influence has been mostly one-sided, except perhaps in the 5th and 6th centuries B.C., where disputes at the market place or in tribunals in Greece seem to have stimulated a lot of reflection among sophistic philosophers on such topics as language and truth. Most of the time it was logic that influenced legal thinking, but in the last 50 years logicians began to be interested in normative concepts and hence in law"--